2023
DOI: 10.1055/a-1990-0509
|View full text |Cite
|
Sign up to set email alerts
|

Sessile serrated lesion detection rates continue to increase: 2008–2020

Abstract: Background and study aims We assessed sessile serrated lesion detection rate (SSLDR) at a large academic medical center from 2008 to 2020 and modeled a local, aspirational target SSLDR. We also assessed SSLDRs among all gastroenterology fellows to better understand the relationship between SSLDRs and total colonoscopies performed. Patients and methods SSL-positive pathology results were flagged from a dataset composed of all screening colonoscopies for average-risk patients from 2008 to 2020. Unadjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…The SSL detection rates were lowest at the beginning of the study period, 0.37% in 2008 increasing to 7.94% in 2020. SSL detection rate was also found to be lower for first year fellows compared to second and third-year fellows [43]. Such improvement of SSL detection rate over the past two decades based on increased recognition of the serrated polyp pathway to CRC may have contributed to decreasing rates of CRC incidence during this time.…”
Section: Future Directionsmentioning
confidence: 86%
“…The SSL detection rates were lowest at the beginning of the study period, 0.37% in 2008 increasing to 7.94% in 2020. SSL detection rate was also found to be lower for first year fellows compared to second and third-year fellows [43]. Such improvement of SSL detection rate over the past two decades based on increased recognition of the serrated polyp pathway to CRC may have contributed to decreasing rates of CRC incidence during this time.…”
Section: Future Directionsmentioning
confidence: 86%
“…The annual trends were 1.8% in 2015, 2.5% in 2018, and 4.2% in 2022, indicating an upward trend over time. Previous reports have shown that the prevalence of SSLs increased over time [4,5,8]. One possible reason for this increase over time was that the concept of serrated lesions and their recognition as potentially malignant lesions has been disseminated; endoscopists have become more careful in their search for serrated lesions, and the rate at which they resect lesions they recognize has also increased.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of SSL has been reported to vary in recent reports between 2 and 10%. [4][5][6][7][8] A prospective study from Japan indicated that the prevalence of SSL was approximately 5% [9]. The proportion of SSLD and cancer in SSL (SSL-cancer) in patients with SSL has been reported as follows: approximately 5-14% for SSLD and 0.9-1.3% for SSL-cancer [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,12,23] This relatively high SDR is not unexpected, given the increasing awareness and recognition of SSLs, as demonstrated by the steady increase of SDR since 2008. [25] Furthermore, in a retrospective analysis of the training and evaluation sets of this CADe system (unpublished results), we found that 11% of the used lesions were diagnosed as SSLs. This relatively large proportion of SSLs in the training set may have contributed to our significant increase in the detection of these notably hard-to-detect lesions.…”
mentioning
confidence: 90%